2019
DOI: 10.1159/000501075
|View full text |Cite
|
Sign up to set email alerts
|

Ustekinumab with Intravenous Infusion: Results in Hidradenitis Suppurativa

Abstract: Adalimumab is the only approved biological therapy for hidradenitis suppurativa (HS). The last published recommendations support the use of other off-label biologic therapies. We report on a multicentric retrospective review of patients with HS treated with an ustekinumab dosing schedule of intravenous infusion adjusted by weight, followed by a subcutaneous maintenance dose of 90 mg every 8 weeks, as recently approved for Crohn’s disease. The minimal follow-up period required for inclusion was 16 weeks. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 7 publications
0
35
0
2
Order By: Relevance
“…A retrospective study showed moderate efficacy of ustekinumab in HS, with similar outcomes to this study (50% HiSCR). 4 Ustekinumab may be considered safe, as no adverse effects were reported in any of the published cases. The main limitations of this study are low number of patients, short follow-up period, use of concomitant medication during treatment with ustekinumab and lack of a control group.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A retrospective study showed moderate efficacy of ustekinumab in HS, with similar outcomes to this study (50% HiSCR). 4 Ustekinumab may be considered safe, as no adverse effects were reported in any of the published cases. The main limitations of this study are low number of patients, short follow-up period, use of concomitant medication during treatment with ustekinumab and lack of a control group.…”
Section: Discussionmentioning
confidence: 90%
“…Despite of the lack of randomized clinical trials that support the efficacy and safety of ustekinumab in HS, some case reports and case series have been published in the literature [3][4][5][6][7][8][9] ; to the best of our knowledge, 49 cases have been published to date. The dosage used was variable, but most of the patients received the psoriasis dosage regimen.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of patients in whom HS had a very large or extremely large effect on daily life decreased from 71% at the beginning of the study to 59% [90]. A retrospective review ( n = 14) of ustekinumab infused intravenously followed by subcutaneous maintenance dosing found that 71% of patients experienced ≥30% improvement in DLQI and visual analog pain score [91]. A systematic review of ustekinumab use in HS found that 34/45 patients (76%) had improvement in physician-reported clinical outcomes and that 38/45 patients (84%) reported symptomatic improvement [225].…”
Section: Medical Management Of Hsmentioning
confidence: 99%
“…In 71.4% of patients, DLQI and VAS improved irrespective of achievement of HiSCR, while two patients did not respond. No ustekinumab‐related adverse effects were reported 43 …”
Section: Treatment With Biologicsmentioning
confidence: 99%
“…Blok et al 43 treated 12 patients with subcutaneous ustekinumab in an open‐label trial. Their dosing was 45 or 90 mg ustekinumab at weeks 0, 4, 16, and 28.…”
Section: Treatment With Biologicsmentioning
confidence: 99%